MODEL OF FORMATION OF TAX OBLIGATIONS OF ENTERPRISES - Abdusherozov Abdullo Baxtiyorovich (Ecominds Press, 2025)
In the article, at the current stage of economic liberalization and modernization in the Republic of Uzbekistan, the system of tax obligations of enterprises and measures for effective management of their tax opportunities, as well as their specific features, are scientifically justified.
Keywords: Tax system, taxes, taxation, tax administration, tax regulation, taxpayer.